2021
DOI: 10.1001/jamanetworkopen.2021.1001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selective Survival and Sex/Gender Differences in Dementia Incidence Using a Simulation Model

Abstract: Key Points Question Can selective survival plausibly explain reported sex/gender differences in dementia incidence? Findings In this decision analytical model of 100 000 simulated adults aged 50 years and without dementia at baseline, sex/gender differences in dementia incidence consistent with literature (ie, 15%-20% elevated risk for women aged ≥85 years) were only observed in the presence of moderate to strong effects of selective survival characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 44 publications
1
33
1
Order By: Relevance
“…264 Recent studies have supported the notion that selection bias contributes to reports of sex and gender differences in Alzheimer's dementia. 273 More research is needed to support this interpretation.…”
Section: Differences Between Women and Men In The Prevalence And Risk...mentioning
confidence: 99%
See 3 more Smart Citations
“…264 Recent studies have supported the notion that selection bias contributes to reports of sex and gender differences in Alzheimer's dementia. 273 More research is needed to support this interpretation.…”
Section: Differences Between Women and Men In The Prevalence And Risk...mentioning
confidence: 99%
“…278,279 Other societal gender differences may also be at play, such as differences in occupational attainment between men and women, with a recent study showing that women who participated in the paid workforce earlier in life had better cognitive outcomes after age 60. [280][281][282] It is unclear whether genetic risk operates differently in women and men in the development of, or susceptibility to, Alzheimer's pathology. 283 A number of studies have shown that the APOE-e4 genotype, the best known common genetic risk factor for Alzheimer's dementia, may have a stronger association with Alzheimer's dementia 284,285 and neurodegeneration 286 in women than in men.…”
Section: Differences Between Women and Men In The Prevalence And Risk...mentioning
confidence: 99%
See 2 more Smart Citations
“…The UK dementia report states that more females have AD and that this trend is likely to remain with a F:M ratio of approximately 2 to 1 in the projected dementia incidence for 2051 [ 13 ]. Although it has been recently reported that selective survival may contribute to sex/gender differences in dementia incidence, this does not preclude the additional contributions from biological mechanisms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%